ECONOMETRIC ANALYSIS OF BANK ASSET EFFICIENCY (American Journal of Business Management, Economics and Banking, 2025)
This article examines the content and essence of bank assets, the opinions of foreign economists on this issue. An econometric analysis of commercial bank assets based on various models is also carried out, and a general conclusion is given.